Stress Management in Emergency Nurses during the COVID-19 Pandemic: Scooping Article - Rohimah, Annisa'i; Prakoso, Adi Buyu; Kusuma, Rahmah Yanita; Jamil, Sobran; Rini, Sri Setiya; Alim, Syahirul (Jurnal Keperawatan Soedirman, 2022)
Nurses are health professionals on the front lines during the COVID-19 pandemic, especially those in the ER, where nurses are the key to controlling virus transmission. This article aims to do a scooping review on how to manage stress in emergency room nurses during the COVID-19 pandemic. This Scooping review explores the literature from the point of view of relevance by assessing the quality of the research, then the data is mapped to identify the main themes found in the literature. We observed that stress on nurses is a burden of excess factors, having a family or children, lifestyle changes, lack of access to PPE, lack of self-confidence, nurses also have feelings and fatigue. We also observed how nurses managed stress, namely strengthening training, positive spiritual coping, social support, and access to mental health services.